(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2020)
COVID-19 usually presents with fever, coughs dyspnea, myalgia, and fatigue and may infect people of any age though older people with co morbidities are more vulnerable. But many carriers do not present any symptoms. Operating on undiagnosed COVID-19 patients may cause exposure of medical staff in ward and theatre.A cross sectional was done on 100 consecutive cases suffering from oral and maxillofacial pathologies from 20th May 2020 to 28th August 2020, recruited from Oral and Maxillofacial Surgery department of Dhaka Dental College Hospital and Square Hospitals Ltd, Dhaka, Bangladesh. Out of 100 cases, 7 were affected (7%) by COVID 19 confirmed by RT-PCR in pre-operative screening.Preoperative COVID 19 screening of asymptomatic patients should be considered to improve patient and provider safety and reduce the cost of resource. J Bangladesh Coll Phys Surg 2020; 38(4): 229-231